Pacific strife the great powers and their political and economic rivalries in Asia and the Western Pacific 1870-1914 - Dijk, C. van (Amsterdam University Press, 2015)
Kees van Dijk traces the emergence of superpowers during the colonial race and analyzes their conduct as they struggled for territory.